Improvement of Diabetes Mellitus Symptoms by Intake of Ninjin'yoeito - Hosogi, Shigekuni; Ohsawa, Masahiro; Kato, Ikuo; Kuwahara, Atsukazu; Inui, Toshio; Inui, Akio; Marunaka, Yoshinori (Frontiers in Nutrition, 2018)
Diabetes mellitus is a well-known common disease and one of the most serious social problems in the worldwide. Although various types of drugs are developed, the number of patients suffering from diabetes mellitus is still increasing. Ninjin'yoeito (NYT) is one of formulas used in Japanese traditional herbal medicines for improving various types of metabolic disorders. However, the effect of NYT on diabetes mellitus has not yet been investigated. In the present study, we tried to clarify the action of NYT on the serum glucose level in streptozotocin (STZ)-induced diabetic mice. We found that intake of NYT decreased the serum glucose level and increased insulin sensitivity in STZ-induced diabetic mice. NYT treatment also improved acidification of the interstitial fluid around skeletal muscles found in STZ-induced diabetic mice, while the interstitial fluid acidification has been reported to cause insulin resistance. Furthermore, in the proximal colon of STZ-induced diabetic mice, NYT treatment showed a tendency to increase the expression of sodium-coupled monocarboxylate transporter 1 (SMCT1), which has ability to absorb weak organic acids (pH buffer molecules) resulting in improvement of the interstitial fluid acidification. Based on these observations, the present study suggests that NYT is a useful formula to improve hyperglycemia and insulin resistance via elevation of interstitial fluid pH in diabetes mellitus, which might be caused by increased absorption of pH buffer molecules (SMCT1 substrates, weak organic acids) mediated through possibly elevated SMCT1 expression in the proximal colon.